Metastasis of parotid adenocarcinoma at the cervical thoracic spine. Case report - Pérez da Rosa, Sandra; Tambe, Anant (Revista Argentina de Neurocirugía, 2024)
Background. The authors report a case of parotid adenocarcinoma with metastasis to the spine, this being the second case found in the literature, and the first of cervico-thoracic location. Objectives. To communicate the difficulties that the multidisciplinary team had to face in managing the patient, given the exceptional nature of the case. Case description. A 48-year-old patient who presents with left otalgia of 2 years’ duration without obvious organic cause. During examination by a dentist, a left parotid tumor was evident. Cervical MRI shows lytic metastatic lesions in the cervico-thoracic spine with collapse of the body of C6 and spinal cord compression. After her evaluation, it was determined that resection of the parotid tumor was not feasible given the instability of the cervical spine. Surgery. In the first stage, a corpectomy of C6 and C7 was performed with anterior stabilization with cage, plate and screws; and in a second stage a posterior fixation from C5-T2 with bars and screws. Histopathological analysis reported a poorly differentiated adenocarcinoma. The postoperative complication was an anterior pseudomeningocele in the cervical region, which prolonged convalescence. She received adjuvant radiotherapy, despite which she presented an unfavorable evolution with a survival of 12 months. Conclusion. The authors report a case of adenocarcinoma metastasis to the cervico-thoracic spine (this being the second reported in the literature) describing the difficulties encountered in making the histopathological diagnosis, treatment and prognosis.